ProZone3 (2008)
ProZone3 is a comprehensive reproduction of a live game. The data generated from this powerful software provides a high-quality assembly of physical, tactical and statistical information presented in multiple formats. The result is a phenomenal interactive coaching and analysis tool that allows you to view every movement, interaction and the total contribution of both your team`s players as well as those of the opposition - a truly invaluable asset in the world of modern football. ProZone have several technologies that enable the capture of performance affecting information. Data is captured from either standard video sources or via a set of installed cameras offering enhanced analysis.